GENDER BASED COMPARATIVE STUDY OF THE QUALITY OF LIFE OF PEOPLE LIVING WITH HUMAN IMMUNODEFICIENCY VIRUS (PLHIV) ON ANTIRETROVIRAL THERAPY (ART) - Khan, Iqra Hamid; Kanathasan, Jayasree S; Das, Sreemoy Kanti; Gohar, Awais (Journal of Ayub Medical College Abbottabad, 2026)
Background: Quality of life of people living with HIV is considered important component of HIV care particularly in settings like Pakistan where treatment access and gender disparities continue to determine the health outcomes despite advancements in treatment regimens. This study aims to compare Health Related-QoL (HR-QOL) among male, female, and transgender individuals living with HIV on ART. Methods: A cross-sectional study was conducted at the HIV/AIDS treatment center of Mayo Hospital, Lahore, between February and July 2024. A sample of 384 participants (221 males, 151 females, and 12 transgender individuals) was selected using non-probability consecutive sampling. Data were collected using the HIV/AIDS-Targeted Quality of Life (HAT-QOL) and SF-36 surveys. Statistical analysis included Chi-square tests for categorical variables and ANOVA for continuous variables, with significance set at p < 0.05. Results: Out of 384 participants, 57.55% were male, 39.32% female, and 3.13% transgender. A significant difference in social status was observed across gender groups (p = 0.020). HRQoL domains differed significantly by gender; transgender individuals reported better overall function (76.11 ± 23.78) compared to females (69.47 ± 22.62) and males (74.1± 23.5), p = 0.001. Multivariate regression showed that health worries had the strongest association with HRQoL among transgender individuals (standardized β = 0.567, 95% CI: 0.09–0.30), compared to males (β = 0.432) and females (β = 0.527), emphasizing the differential impact on quality of life. Conclusion: Gender-specific differences in HRQOL among PLHIV needs considerations for gender-sensitive healthcare approaches to improve overall well-being and quality of life for all individuals living with HIV.